Determinación de valores hematológicos en el perro “Ganacho” localizado en la zona sur del Ecuador - Viñan Capa, Wilmer Alexander (2024)
The “Ganacho” or cattle dog plays an important role in the care of goats in the dry forest region of the southern part of the country. An essential factor is to know about the hemogram in these canines and the variability of hematological values influenced by factors such as age, sex and influenced. The purpose of this research was to determine hematological values and to characterize morphologically morphological the red blood cells in “Ganachos” dogs from the dry forest of the province of Loja. Five ml of blood was taken from the cephalic vein and the sample was placed in vacutainer tubes with anticoagulant (EDTA), samples were taken from 54 Creole dogs between 1 and 15 years of age, whose habitat was the different regions of the dry forest, were sampled using the Veterinary Laboratory of the National University of Loja for the development of blood analysis. A statistical analysis of variance (ANOVA) was used, considering p values (<0.05) as statistically significant. The results obtained show that in the variables sex, age, altitude did not present significant differences at p value (<0.05), in terms of hemoglobin, hematocrit, erythrocytes, platelets and lymphocytes, platelets and lymphocytes. In case of leukocytes, there was a statistical significance (p: 0.038), in relation to the age of the animals with a value of 10.4 g/dL x109 in young animals, 11.85 g/dL x109 in adults and 8.26 g/dL x109 in geriatrics. The values of hemogram obtained in “Ganachos” dogs are lower than the reference values found in other studies. As for the morphological characterization of the erythrocytes in the variables analyzed did not show significance in this study, in addition the measures obtained in the morphological characterization of erythrocytes in these dogs, the measures are within the reference ranges established in the literature.